![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)(-3)×(-5)-45÷(-15) (2)3×(-4)+(-28)÷7 (3)(-2.5)×(-4.8)÷(-1.6)
3个回答
展开全部
(1)(-3)×(-5)-45÷(-15)
=15+3
=18
(2)3×(-4)+(-28)÷7
=-12-4
=-16
(3)(-2.5)×(-4.8)÷(-1.6)
=12÷(-1.6)
=-7.5
(4)-3/4×[-3的平方×(-2/3)的平方-(-2)的3次方]
=-3/4×[-9×(-4/9)+8]
=-3/4×[4+8]
=-3/4×12
=-9
=15+3
=18
(2)3×(-4)+(-28)÷7
=-12-4
=-16
(3)(-2.5)×(-4.8)÷(-1.6)
=12÷(-1.6)
=-7.5
(4)-3/4×[-3的平方×(-2/3)的平方-(-2)的3次方]
=-3/4×[-9×(-4/9)+8]
=-3/4×[4+8]
=-3/4×12
=-9
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询